Enhanced photoresponse by plasmon resonance in Ni-WS2/Si photodiode. (January 2022) - Patel, Meswa; Pataniya, Pratik M.; Sumesh, C.K.
Highlights: High photoresponsivity of 0.87 A/W have been achieved. Detectivity of 1.8 × 10 11 Jones and EQE of 161% are realized at −1 V bias. Response time of found to be about 63 ms. Photoresponse is stable for prolonged illumination of 3000 s. Abstract: Two-dimensional transition metal dichalcogenides have shown promising photodetection applications in visible region due to strong light matter interaction. Herein, we have attempted to produce Ni-WS2 nanocomposite with improved surface plasmon resonance assisted light absorption for subsequent fabrication of Ni-WS2 /Si heterojunction. Fabricated Ni-WS2 /Si photodiode shows obvious current rectification with 1.1 ideality factor. Photodiodes have shown obvious photovoltaic activities under illumination of visible light and remarkable photoswitching ability with high photoresponsivity of 0.87A/W, specific detectivity of 1.8 × 10 11 Jones and external quantum efficiency of 161% at -1 V bias. Encouragingly, photodiodes have served nicely as fast and highly stable photoswitch with response time of as low as 63 ms. Photoswitching abilities have been found to be stable even after prolonged illumination time of 2500s as well as over several cycles of periodic illumination. Overall, present finding advocates a significant development in opto-electronics due to plasmonic improvement and optimized device configuration. Graphical abstract: Image, graphical abstract